Cortical sources of resting state electroencephalographic rhythms probe brain function in naïve HIV individuals. Issue 2 (February 2018) - Babiloni, Claudio; Noce, Giuseppe; Pennica, Alfredo; Onorati, Paolo; Capotosto, Paolo; Del Percio, Claudio; Roma, Paolo; Correr, Valentina; Piccinni, Elisa; Toma, Ginevra; Soricelli, Andrea; Di Campli, Francesco; et al.
Highlights: Resting EEG rhythms slightly correlate with neuropsychological scores in HIV subjects. These rhythms also show moderate discrimination between HIV and control individuals. EEG markers unveil HIV neuroinvasion effects at the individual level. Abstract: Objective: Here we evaluated the hypothesis that resting state electroencephalographic (EEG) cortical sources correlated with cognitive functions and discriminated asymptomatic treatment-naïve HIV subjects (no AIDS). Methods: EEG, clinical, and neuropsychological data were collected in 103 treatment-naïve HIV subjects (88 males; mean age 39.8 years ± 1.1 standard error of the mean, SE). An age-matched group of 70 cognitively normal and HIV-negative (Healthy; 56 males; 39.0 years ± 2.0 SE) subjects, selected from a local university archive, was used for control purposes. LORETA freeware was used for EEG source estimation in fronto-central, temporal, and parieto-occipital regions of interest. Results: Widespread sources of delta (<4 Hz) and alpha (8–12 Hz) rhythms were abnormal in the treatment-naïve HIV group. Fronto-central delta source activity showed a slight but significant (p < 0.05, corrected) negative correlation with verbal and semantic test scores. So did parieto-occipital delta/alpha source ratio with memory and composite cognitive scores. These sources allowed a moderate classification accuracy between HIV and control individuals (area under the ROC curves of 70–75%). Conclusions: Regional EEG abnormalities in quiet wakefulness characterized treatment-naïve HIV subjects at the individual level. Significance: This EEG approach may contribute to the management of treatment-naïve HIV subjects at risk of cognitive deficits.